تحليل الخطاب العربي المعاصر في ضوء نظرية التلقي ومعيار القصدية : رواية "موسم الهجرة إلى الشمال" للطيب صالح أنموذجا - صلاح الدين، منير الدين الرياضي (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study aims at analyzing the theories of Receptionality and Intentionality, according to the modern Arabic speech in Al-Tayyib Salih's novel entitled Season of Migration to the North. The theory of Receptionality is one of the modern theories that broke the silence about the marginalization suffered by the reader of a text. This also concerns about the interest of the reader and his expectation from a text. This study therefore, wishes to engage in highlighting the essential features of theory of Receptionality with a brief glance at the historical dimension of the factors that influenced its emergence and the analysis of some of its elements in Season of Migration to the North. The analysis were based on Aesthetic Reception, Horizon Expectation, Aesthetic Response and Reading Acts. The second facet on which the study is based on was analysis of Intentionality, which is one of the text standards discovered by De Beau grand. The study therefore, deals with the analysis of the tendency of intent and speech acts with a special consideration to Statement and Construction (الخبر والإنشاء) to determine the direct and indirect power of speech and the meanings emanating from the two concepts, in addition to the analysis of the apparent and hidden purposes of communication embedded in the speaker's intention. In performing this academic task, the researcher adopts an analytical approach